Measurement and Analysis of the Financial Costs of Licensing Rounds and their Implications on Addressing Imbalances in the Sectors of the Iraqi Economy for the Period (2004-2020) - Alyaa Suhail Najm; Adeeb Gassim Shandi (Migration Letters, 2023)
The oil sector serves as a crucial lifeline to the Iraqi economy. Any investment and progress within this sector have far-reaching implications for other economic sectors. Considering the deterioration and lack of development in the sector’s infrastructure due to neglect and wars, this study seeks to address one of the most pressing challenges confronting Iraq’s oil industry. The research delves into the debate surrounding the oil contracts entered into by the Iraqi Ministry of Oil in 2010. On one hand, dissenting opinions perceive these contracts as leaning closer to a production-sharing approach, while proponents view them as contracts centered around services rendered by foreign oil companies. Consequently, the research aims to analyse the landscape of foreign direct investment within Iraq’s oil sector and conduct a detailed study of Iraqi oil service contracts. The study comprehensively outlines all associated costs, compares them with oil revenues, and reveals the magnitude of losses incurred during the 2004-2020 period. The research’s objective is to validate the hypothesis that licensing rounds have not significantly impacted the rectification of economic imbalances in Iraq. Although these rounds have contributed to the development of export-oriented production capacities within the oil sector, their impact remains limited due to the Gross Domestic Product’s sensitivity to oil prices rather than production quantities. The study concludes that these contracts are geared towards extracting substantial oil quantities without local investment possibilities. As a result, there is wastage of this valuable resource and neglect of the rights of future generations in the face of depleting resources. The research highlights the necessity of formulating a future oil policy guided by an independent national vision and economic policies focused on modernising the Iraqi oil sector. These policies should be well-defined and serve as guidance for the utilization of oil resources, primarily aiming to promote economic growth and employment.